The RNA m6A writer METTL3 in tumor microenvironment: emerging roles and therapeutic implications - Su, Weiqi; Che, Lin; Liao, Wenting; Huang, Huilin (Frontiers in Immunology, 2024)
The tumor microenvironment (TME) is a heterogeneous ecosystem comprising cancer cells, immune cells, stromal cells, and various non-cellular components, all of which play critical roles in controlling tumor progression and response to immunotherapies.Methyltransferase-like 3 (METTL3), the core component of N 6 -methyladenosine (m 6 A) writer, is frequently associated with abnormalities in the m 6 A epitranscriptome in different cancer types, impacting both cancer cells and the surrounding TME. While the impact of METTL3 on cancer cells has been extensively reviewed, its roles in TME and anti-cancer immunity have not been comprehensively summarized. This review aims to systematically summarize the functions of METTL3 in TME, particularly its effects on tumor-infiltrating immune cells. We also elaborate on the underlying m 6 Adependent mechanism. Additionally, we discuss ongoing endeavors towards developing METTL3 inhibitors, as well as the potential of targeting METTL3 to bolster the efficacy of immunotherapy.